A DSGE model of fiscal stabilizers and informality in Sub-Sahara Africa - Eric Amoo Bondzie; Mark Kojo Armah (Cogent Economics & Finance, 2022)
This paper investigates the effects of fiscal impulses on macroeconomic variables within a New-Keynesian DSGE framework featuring an informal economy that allows for the examination of the effectiveness of automatic stabilizers in stimulating some selected sub-Saharan African (SSA) economies during crises. Stabilizers were modelled such that fiscal instruments react to their own lagged values and the official sector output. The results indicate that tax hikes lead to sizeable tax evasion and reallocation of factor inputs from the official sector to the shadow sector making the standard aggregate estimates of fiscal policies ineffective while government spending shocks slow down activities in the shadow sector. The findings also showed that automatic stabilizers on government spending (income taxes) stabilized the economy by reducing (raising) output levels even in the presence of the shadow economy. For policy implications, effective implementation of government policies should incorporate the informal sector in macroeconomic modelling, especially for countries with a large informal sector.
Keywords: D58; E12; E26; E52; E62; 330; automatic stabilizers; DSGE models; Fiscal policy; informality; Sub-Sahara Africa